The Influence of Body Mass Index on Outcomes After Hip Arthroscopic Surgery With Capsular Plication for the Treatment of Femoroacetabular Impingement. (August 2017) - Saltzman, Bryan M.; Kuhns, Benjamin D.; Basques, Bryce; Leroux, Timothy; Alter, Jennifer; Mather, Richard C.; Salata, Michael J.; Nho, Shane J.
Background: It remains unknown how variations in body mass index (BMI) influence outcomes after primary hip arthroscopic surgery with capsular plication for femoroacetabular impingement (FAI). Purpose: To evaluate the effect that abnormal BMI (namely, overweight, obese, morbidly obese, and underweight) versus normal weight has on patient-reported clinical outcomes more than 2 years postoperatively from primary hip arthroscopic surgery with capsular plication by a single surgeon. Study Design: Cohort study; Level of evidence, 3. Methods: A clinical repository containing patients undergoing primary hip arthroscopic surgery for FAI between January 1, 2012, and January 1, 2014, with a minimum 2-year follow-up was queried. Outcome measures included the Hip Outcome Score (HOS)–Activities of Daily Living (ADL), HOS-Sports, modified Harris Hip Score (mHHS), visual analog scale (VAS) for pain; satisfaction, and Patient Acceptable Symptomatic State (PASS) for the HOS-ADL; scores were collected preoperatively and at 3 months, 1 year, and minimum 2 years postoperatively. Included patients were segregated by preoperative BMI into the following categories: underweight (<18.5 kg/m 2 ), normal (18.5-24.9 kg/m 2 ), overweight (25.0-29.9 kg/m 2 ), obese (30.0-34.9 kg/m 2 ), and morbidly obese (≥35.0 kg/m 2 ). A multivariate logistic regression model controlling for patient demographics and disease severity was used to identify independent associations between BMI categories and outcomes. A Bonferroni adjustment lowered the threshold for significance to P < .01. Results: There were 409 hips in 381 patients appropriate for study inclusion: 7 underweight, 197 normal BMI, 130 overweight, 31 obese, and 16 morbidly obese. The mean age was 33.1 ± 12.1 years, with 232 (61%) female patients. At 2 years postoperatively, significant differences in the trend among HOS-ADL, HOS-Sports, and mHHS scores were evident, with normal BMI patients, followed by underweight patients, demonstrating greater scores than their overweight, obese, and morbidly obese counterparts. Obese patients demonstrated lower satisfaction scores than normal BMI patients. Overweight, obese, and morbidly obese patients had lower improvements in VAS pain scores compared with normal BMI patients. Increasing BMI (not subdivided into the 5 BMI categories) was associated with a higher infection risk (mean BMI for infections: 32.3 ± 9.8 kg/m 2 vs mean BMI for noninfections: 25.2 ± 4.8 kg/m 2 ; P = .0035). However, with multivariate analysis, no significant differences in patient clinical outcomes between the BMI categories met the threshold for significance. Among obese patients (BMI ≥30.0 kg/m 2 ), no specific risk factors were found to be significantly associated with decreases in the change in VAS, HOS-ADL, HOS-Sports, mHHS, satisfaction, or PASS for the HOS-ADL scores. However, because of the small cohort sizes at the extremes of the BMI categories, this analysis may have been underpowered to identify a significant difference in underweight or morbidly obese patients. Conclusion: In the current cohort, there were multiple potential confounding variables, and while some clinical differences were observed initially (higher HOS-ADL, HOS-Sports, and mHHS scores for normal BMI patients than overweight and obese patients at 2 years postoperatively; lower satisfaction scores for obese patients than normal BMI patients; and lower improvement in VAS pain scores for overweight, obese, and morbidly obese patients when compared with normal BMI patients), after multivariate analysis, no associations were observed between BMI and clinical outcomes after hip arthroscopic surgery with capsular plication for FAI.